Effect of Aging on the Vocal Muscle - Peres, André de Carvalho Sales [UNESP]; Pessim, Adriana Bueno Benito [UNESP]; Rodrigues, Sergio Augusto [UNESP]; Martins, Regina Helena Garcia [UNESP] (Elsevier, 2022)
Introduction: Sarcopenia is a common and natural condition in the elderly, and leads to loss of muscle mass and function. In the presbylarynx there is atrophy of the vocal folds, however the degree of vocal muscle atrophy is poorly studied and the results are contradictory. Aims: The aim of this study was to evaluate the effect of aging on the vocal muscle (thyroarytenoid muscle). Methods: Thirteen larynxes removed during necropsy from 13 cadavers were included into two age groups: Control group – G1 (n5), between 25 and 40 years; Elderly Group - GI (n-8), aged 70 years or older. The vocal folds were dissected and prepared for scanning electron microscopy, ensuring a cross-section in the musculature area to allow measurements of muscle fiber parameters. Images were analyzed and photographed at different magnifications. Through the ImageJ software, ten distinct fields of each part were selected. Parameters studied: area, perimeters and diagonals of the thyroarytenoid muscle bundles of both groups. Results: The cross-sectional areas, perimeters and diagonals of the muscle fibers of the thyroarytenoid muscle of the elderly group were significantly smaller than those of the control group. Conclusion: We demonstrated that the vocal muscle is affected in the presbylarynx, with a reduction of its muscle fibers, corresponding to muscle atrophy. However, these findings may not be directly related to vocal symptoms because the patient may develop muscle compensatory mechanisms capable of reducing glottic insufficiency
Keywords: Aging; Electron microscopy; Etiology; Human; Muscle atrophy